2019
DOI: 10.1007/s10995-018-02705-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Steroid Hormone Concentrations in Early Pregnancy: Results from a Multi-Center Cohort

Abstract: Objectives: To identify factors predicting maternal sex steroid hormone concentrations in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Statistically significant difference was found in the serum values of DHEA and androstenedione considering maternal parity, with lower values in the group of multiparous woman. The results are consistent with available research by Arslaan et al 33 , Musey et al, 34 Toriola et al, 35 and Barrett et al 36 So far, no explanation has been found for differences in the steroid hormone profile depending on parity. Possible explanations include differences in placental size and its activity in primiparous and multiparous women, differences in the concentration of hormone‐binding proteins in primiparous and multiparous mothers, which reduces hormone bio availability and their function, in the modulation of hormone receptor expression, and in altered maternal hormone metabolism 33,36 …”
Section: Discussionsupporting
confidence: 92%
“…Statistically significant difference was found in the serum values of DHEA and androstenedione considering maternal parity, with lower values in the group of multiparous woman. The results are consistent with available research by Arslaan et al 33 , Musey et al, 34 Toriola et al, 35 and Barrett et al 36 So far, no explanation has been found for differences in the steroid hormone profile depending on parity. Possible explanations include differences in placental size and its activity in primiparous and multiparous women, differences in the concentration of hormone‐binding proteins in primiparous and multiparous mothers, which reduces hormone bio availability and their function, in the modulation of hormone receptor expression, and in altered maternal hormone metabolism 33,36 …”
Section: Discussionsupporting
confidence: 92%
“…Finally, we utilized gold standard LC−MS/MS methods for hormone quantification which represent a considerable advance compared to prior methods with poor sensitivity for hormones such as androgens that are present at very low doses in adult women. 32 Extensive data collection from participating mothers and children allowed us to adjust for confounding and precision variables, which is an advance upon the many studies in this area that present only unadjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…26,31 A final complication is that the standard radioimmunoassay techniques utilized by many studies may have inadequate sensitivity to accurately measure androgens present in extremely low concentrations, such as those observed in pregnant women. 32 Beyond digit ratio, alternative indirect measures of prenatal androgen exposure have been proposed, most notably anogenital distance (AGD), an anatomic measure from the anus to the genitals. Like digit ratio, AGD is readily measured with standard calipers.…”
Section: Introductionmentioning
confidence: 99%
“…In pre-menopausal women, increased BMI is associated with anovulation, reducing lifetime exposure of circulating oestrogen and progesterone [44], thus lowering breast cancer risk [45] and increasing uterine cancer risk [46]. Higher maternal BMI is also associated with reduced oestrogen exposure in utero [47], which is protective against testicular cancer [48] and in males, elevated BMI reduces serum testosterone [49], reducing prostate cancer risk. Our findings of causal roles of BMI in regulating risk of certain reproductive and hormone-responsive cancers are therefore biologically plausible although the mechanistic links need to be assessed further.…”
Section: Discussionmentioning
confidence: 99%